Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T18:43:02+01:00
-3/4 -6* (3/20 -0,25):1/2 = -¾ -6 × ( 3/20 - ¼) ÷ ½ = -¾ - 6 ×
(3/20 - 5/20)÷ ½= -¾ - 6 × (-2/20) ÷ ½ = -¾ - (-12/20) ÷ ½ = -15/20 - (-12/20) ÷ ½ = -15/20 - (-12/20) × 2/1 = -15/20 - (-24/20) = -15/20 + 24/20 = 9/20

Mam nadzieję, że pomogłam !
Powodzenia :)
2010-02-01T18:45:39+01:00
-3/4 -6*(3/20 -0,25):1/2= 9/20
2010-02-01T18:49:29+01:00
-¾-6*(3/20-1/4):1/2 = -¾-6* (3/20-5/20):1/2 = -¾-6*(-1/10):1/2 = -¾ +6/10 : 1/2 = -¾ + 6/10 * 2 = -¾ + 6/5 = -15/10 + 24/20 = 9/20